Exploring the need for a new UK occupational therapy intervention for people with dementia and family carers: Community Occupational Therapy in Dementia (COTiD). A focus group study. (2nd July 2016) - Hynes, Sinéad M; Field, Becky; Ledgerd, Ritchard; Swinson, Thomas; Wenborn, Jennifer; di Bona, Laura; Moniz-Cook, Esme; Poland, Fiona; Orrell, Martin
Abstract : Objectives: In the Netherlands, Graff et al. found Community Occupational Therapy in Dementia (COTiD) demonstrated benefits to people with dementia and family carers. In this study, focus groups took place with people with dementia and family carers to explore how to make COTiD relevant to the UK context. Method: Six focus groups (three with people living with dementia ( n = 18) and three with family carers ( n = 21)) took place. Participants were asked for their impressions of the intervention, the extent to which it could meet their needs, and what modifications were needed. Audio-recordings of the groups were transcribed and analysed. Results: Three key themes emerged covering 'loss and living with dementia', 'what helped us', and 'consistency and continuity'. People with dementia and family carers spoke about the impact of their diagnosis on them and their family and what strategies helped. Issues such as timing, follow-up, and the importance of an early intervention in preventing crises were highlighted. There was some concern over the length of the intervention and the disruption it might cause to current schedules. Conclusion: Overall, participants were optimistic about COTiD being used in the United Kingdom if it was to be introduced in a flexible and timely manner, incorporating the needs and existing strategies of the person with dementia. These outcomes have led to changes, such as incorporating more flexibility into COTiD, being made to the intervention prior to its implementation in the United Kingdom.